Thermal, spectroscopic and dielectric investigation of Na2–2xLi2xPbP2O7 glasses. (2nd September 2017) - Abadi, S.; Aride, J.; Benkhouja, K.; Haddad, M.; Taibi, M.
ABSTRACT: The Na2 –2 x Li2 x PbP2 O7 glasses were elaborated using the usual melting method. The amorphous system was analyzed by X-ray diffraction. The effects of the substitution of the Na + ions by the Li + ones on glass transition temperature, crystallization temperature and thermal stability were investigated using differential scanning calorimetry. The kinetics parameters such as activation energy E a of the glass crystallization, the activation energy for crystal growth E G, Avrami exponent n and factor depending on the growth morphology during the process of crystallization m were determined using different models. The IR and Raman spectra are examined in order to show the influence of the composition on the vitreous structure. The dielectric studies were conducted as a function of temperature and frequencies to evaluate the composition effect on the dielectric constant, dielectric loss and ionic conductivity.